1983
DOI: 10.1007/bf00379720
|View full text |Cite
|
Sign up to set email alerts
|

Inter-relationships between type, size and colour of fruits and dispersal in southern African trees

Abstract: The indigenous angiosperm tree flora (1,340 species) of southern Africa was analysed for type, size and colour of fruits and class of biotic dispersal agent (consumer). Species producing fleshy (drupes and berries) and dry (pods, capsules and nuts) fruits account for 52% and 47%, respectively, of the flora. The flora contains about 2.5 times as many berry-producing as drupe-producing species. Based on a log-linear model, fruit type, consumer and fruit size are dependent statistically on each other, whereas fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
85
1
3

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 19 publications
15
85
1
3
Order By: Relevance
“…The proportions of fruit colours appear to be similar to data from elsewhere in Australasia (Willson et al 1989), but distinct from areas such as southern Africa, where there are higher proportions of green and brown fruits, a factor attributable to the importance of large mammals (Gautier-Hion et al 1985, Knight & Siegfried 1983. The proportion of functionally fleshy fruits we recorded is similar to that observed in other tropical regions, and elsewhere in Australasia.…”
Section: Discussionsupporting
confidence: 80%
“…The proportions of fruit colours appear to be similar to data from elsewhere in Australasia (Willson et al 1989), but distinct from areas such as southern Africa, where there are higher proportions of green and brown fruits, a factor attributable to the importance of large mammals (Gautier-Hion et al 1985, Knight & Siegfried 1983. The proportion of functionally fleshy fruits we recorded is similar to that observed in other tropical regions, and elsewhere in Australasia.…”
Section: Discussionsupporting
confidence: 80%
“…This study revealed many similar trends and subtle differences with other studies (Knight & Siegfried 1983, Wheelwright & Janson 1985, Herrera 1987, Dowsett-Lemaire 1988, Willson et al 1989, Corlett 1996, Nakanishi 1996. As reported for other floras (Herrera 1987, Corlett 1996, the frequency distributions of seed number, fruit and seed sizes are highly skewed to the right.…”
Section: Community Patterns In Fruit Morphology and Colorsupporting
confidence: 83%
“…As reported for other floras (Herrera 1987, Corlett 1996, the frequency distributions of seed number, fruit and seed sizes are highly skewed to the right. Similarly, the fruit color spectrum found at Saibadela parallels those found in other communities, with black and red being the most common colors (Knight & Siegfried 1983, Willson et al 1989, Corlett 1996. The predominance of black over red in bird fruits seems to be a characteristic feature of most plant communities (Wheelwright & Janson 1985, Knight & Siegfried 1983, Nakanishi 1996, but it is different from savanna communities (Donatti et al 2007).…”
Section: Community Patterns In Fruit Morphology and Colorsupporting
confidence: 63%
See 1 more Smart Citation
“…Este padrão é também comum em outras regiões subtropicais como em Hong Kong (Corlett 1996) e em localidades na Austrália (Willson et al 1989), em que as aves representam importante papel como dispersoras. Fogem a este padrão as regiões de cerrado (Galetti 2001) e de savana africana (Knighth & Siegfried 1983), nas quais se verifica maior freqüência de frutos mamaliocóricos, associados à presença de mamíferos de grande porte.…”
Section: Discussionunclassified